Quantitative pulmonary perfusion imaging at 3.0 T of 2-year-old children after congenital diaphragmatic hernia repair: initial results - Zöllner, Frank G.; Zahn, Katrin; Schaible, Thomas; Schönberg, Stefan; Schad, Lothar R.; Neff, Wolfgang (European radiology, 2012)
ObjectiveTo investigate whether dynamic contrast-enhanced MR imaging of the lung following congenital diaphragmatic hernia repair is feasible at 3.0 T in 2-year-old children and whether associated lung hypoplasia (reflected in reduced pulmonary microcirculation) can be demonstrated in MRI.MethodsTwelve children with a mean age 2.0 ± 0.2 years after hernia repair underwent DCE-MRI at 3.0 T using a time-resolved angiography with stochastic trajectories sequence. Quantification of lung perfusion was performed using a pixel-by-pixel deconvolution approach. Six regions of interest were placed (upper, middle and lower parts of right and left lung) to assess differences in pulmonary blood flow (PBF), pulmonary blood volume (PBV) and mean transit time (MTT) while avoiding the inclusion of larger pulmonary arteries and veins.ResultsThe difference in PBF and PBV between ipsilateral and contralateral lung was significant (P < 0.5). No significant differences could be detected for the MTT (P = 0.5).ConclusionDCE-MRI in 2-year-old patients is feasible at 3.0 T. Reduced perfusion in the ipsilateral lung is reflected by significantly lower PBF values compared with the contralateral lung. DCE-MRI of the lung in congenital diaphragmatic hernia can help to characterise lung hypoplasia initially and in the long-term follow-up of children after diaphragmatic repair. Key Points • Congenital diaphragmatic hernia often leads to lung hypoplasia and secondary pulmonary hypertension.• Dynamic contrast-enhanced 3-T magnetic resonance can assess these complications in 2-year-olds.• The affected ipsilateral lung shows reduced perfusion and lower pulmonary blood flow. • Thoracic DCE-MRI helps characterise lung hypoplasia in children after hernia repair.